Induction of cell cycle arrest and apoptosis by betulinic acid-rich fraction from Dillenia suffruticosa root in MCF-7 cells involved p53/p21 and mitochondrial signalling pathway. (26th May 2015) - Foo, Jhi Biau; Saiful Yazan, Latifah; Tor, Yin Sim; Wibowo, Agustono; Ismail, Norsharina; How, Chee Wun; Armania, Nurdin; Loh, Su Peng; Ismail, Intan Safinar; Cheah, Yoke Kqueen; Abdullah, Rasedee
Abstract: Ethnopharmacological relevance: Dillenia suffruticosa (Family: Dilleniaceae) or commonly known as " Simpoh air " in Malaysia, is traditionally used for treatment of cancerous growth including breast cancer. Aim of the study: D. suffruticosa root dichloromethane extract (DCM-DS) has been reported to induce G0 /G1 phase cell cycle arrest and apoptosis in caspase-3 deficient MCF-7 breast cancer cells. The present study was designed to investigate the involvement of p53/p21 and mitochondrial pathway in DCM-DS-treated MCF-7 cells as well as to identify the bioactive compounds responsible for the cytotoxicity of DCM-DS. Materials and methods: Extraction of D. suffruticosa root was performed by the use of sequential solvent procedure. GeXP-based multiplex system was employed to investigate the expression of p53, p21, Bax and Bcl-2 genes in MCF-7 cells treated with DCM-DS. The protein expression was then determined using Western blot analysis. The bioactive compounds present in DCM-DS were isolated by using column chromatography. The structure of the compounds was elucidated by using nuclear magnetic resonance spectroscopy. The cytotoxicity of the isolated compounds towards MCF-7 cells was evaluated by using MTT assay. The percentage of betulinic acid (BA) in DCM-DS was determined by HPLC analysis. Results: The expression of p53 was significantly up-regulated at protein level. The expression of p21 at both gene and protein levels was significantly up-regulated upon treatment with DCM-DS, suggesting that the induction of G 0 / G 1 phase cell cycle arrest in MCF-7 cells was via p53/p21 pathway. Bcl-2 protein was down-regulated with no change at the mRNA level, postulating that post-translational modification has occurred resulting in the degradation of Bcl-2 protein. Overall, treatment with DCM-DS increased the ratio of Bax/Bcl-2 that drove the cells to undergo apoptosis. A total of 3 triterpene compounds were isolated from DCM-DS. Betulinic acid appears to be the most major and most cytotoxic compound in DCM-DS. Conclusion: DCM-DS induced cell cycle arrest and apoptosis in MCF-7 cells via p53/p21 pathway. In addition, DCM-DS induced apoptosis by increasing the ratio of Bax/Bcl-2. Betulinic acid, which is one of the major compounds, is responsible for the cytotoxicity of the DCM-DS. Therefore, BA can be used as a marker for standardisation of herbal product from D. suffruticosa . DCM-DS can also be employed as BA-rich extract from roots of D. suffruticosa for the management of breast cancer. Graphical abstract: